uc.77- Downregulation Promotes Colorectal Cancer Cell Proliferation by Inhibiting FBXW8-Mediated CDK4 Protein Degradation - Zheng, Zhijian; Hong, Dan; Zhang, Xiaodong; Chang, Yixin; Sun, Ning; Lin, Zhenni; Li, Hongyan; Huang, Shirui; Zhang, Ruirui; Xie, Qipeng; Huang, Haishan; Jin, Honglei (Frontiers in Oncology, 2021)
Transcribed ultraconserved regions (T-UCRs) are a new type of long non-coding RNA, and the UCR has 481 segments longer than 200 base pairs that are 100% conserved between humans, rats, and mice. T-UCRs involved in colorectal cancer (CRC) have not been studied in detail. We performed T-UCR microarray analysis and found that uc.77- was significantly downregulated in CRC tissues and cell lines. Ectopic expression of uc.77- significantly inhibited the proliferation of CRC cells in vitro and the growth of xenograft tumors in nude mice in vivo. Mechanistic studies showed that uc.77- competed with FBXW8 mRNA for binding to microRNA (miR)-4676-5p through a competing endogenous RNA mechanism and inhibited the proliferation of CRC cells by negatively regulating CDK4. The present findings highlight the role of the uc.77-/miR-4676-5p/FBXW8 axis in CRC and identify uc.77- as a potential novel target for the treatment of CRC.